How Patriarchy Fails Men: An Analysis of Ken in Barbie (2023) - Irgi Fahrezi; I Wayan Juniartha (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2026)
This study examines the representation of masculinity and femininity in Barbie (2023) by analyzing how gender identity is constructed and contested within its narrative. The research investigates how patriarchal norms shape male self-conception and how female agency resists and redefines those norms. Using a qualitative approach, the study applies R.W. Connell’s theory of hegemonic masculinity to analyze Ken’s dependence on Barbie’s recognition as a reflection of fragile male identity under patriarchy. In addition, bell hooks’ perspective on love, selfhood, and liberation is employed to highlight Ken’s journey toward acknowledging individuality beyond patriarchal validation. The data are drawn from selected dialogues and scenes that capture the tension between dominance, vulnerability, and the search for authentic identity. The findings reveal that the film critiques traditional masculinity while opening space for more inclusive, self-affirming models of gender relations. This study contributes to contemporary gender discourse by showing how popular culture, particularly cinema, can serve as a medium of critical reflection that bridges feminist theory and cinematic representation.